2003
DOI: 10.1074/jbc.m306788200
|View full text |Cite
|
Sign up to set email alerts
|

Residue Gln4863 within a Predicted Transmembrane Sequence of the Ca2+ Release Channel (Ryanodine Receptor) Is Critical for Ryanodine Interaction

Abstract: Despite the pivotal role of ryanodine in ryanodine receptor (RyR) research, the molecular basis of ryanodine-RyR interaction remains largely undefined. We investigated the role of the proposed transmembrane helix TM10 in ryanodine interaction and channel function. Each amino acid residue within the TM10 sequence, 4844 2؉ . Interestingly these two groups of mutants, each with similar properties, are largely located on opposite sides of the predicted TM10 helix. Single channel analyses revealed that mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
(113 reference statements)
3
37
0
Order By: Relevance
“…7, we hypothesize that the side of the TM10 helix containing smaller and less hydrophobic residues is oriented toward the water-filled cavity, whereas the opposite side of the helix is involved in hydrophobic interactions with other helices of the channel. In support of this model, we have shown that TM10 residues such as Phe 4846 [3], Thr 4849 [6], Val 4856 [13], and Gln 4863 [20] are critical for interaction with ryanodine (26). These residues are located on the proposed pore-lining side of the TM10 helix, which is consistent with the notion that the high affinity ryanodine binding site is likely located in the outer vestibule of the RyR channel pore (31).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…7, we hypothesize that the side of the TM10 helix containing smaller and less hydrophobic residues is oriented toward the water-filled cavity, whereas the opposite side of the helix is involved in hydrophobic interactions with other helices of the channel. In support of this model, we have shown that TM10 residues such as Phe 4846 [3], Thr 4849 [6], Val 4856 [13], and Gln 4863 [20] are critical for interaction with ryanodine (26). These residues are located on the proposed pore-lining side of the TM10 helix, which is consistent with the notion that the high affinity ryanodine binding site is likely located in the outer vestibule of the RyR channel pore (31).…”
Section: Discussionsupporting
confidence: 84%
“…On the basis of these findings and the proposed pore model of RyR, it is anticipated that the putative inner helix of the RyR channel pore, TM10, would be involved in channel activation and gating. In line with this hypothesis, we have recently shown that the TM10 sequence contains an important determinant for ryanodine interaction (26) and that ryanodine is able to sensitize the RyR channel to Ca 2ϩ activation (27), suggesting the involvement of TM10 in Ca 2ϩ activation. To test this hypothesis directly, we have mutated each residue in the TM10 sequence and systematically characterized the effects of these mutations on channel activation by caffeine or by Ca 2ϩ .…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Unfortunately, no binding domains are known for caffeine, which also requires tens of millimolar concentrations in other cells, just as in Paramecium (25,48). Putative ryanodine-binding sites normally present in the last C-terminal transmembrane domain (100) are not present in the primary sequence of P. tetraurelia CRC-IV-1 (Fig. 2D), thus explaining their insensitivity.…”
Section: Discussionmentioning
confidence: 99%